Achieving academic promotion: The role of work environment, role conflict, and life balance - Bowering, Elizabeth; Reed, Maureen (Canadian Journal of Higher Education, 2021)
Fifty-two faculty at two Canadian universities were interviewed about the impact of work environment, role conflict, and worklife balance on career-related experiences and decisions to apply for promotion to full professor. Faculty described conflicts between their academic responsibilities of teaching, research, and service (including limited time for research despite long work weeks) as well as work-life imbalance. These issues were often gendered; women took slightly longer to achieve the rank of associate professor, accepted tasks of lower reward value, held decreased expectations for promotion, and experienced workplace conflict and bullying more than their male counterparts. Even so, faculty identified colleagues as a valuable career support. Our data lead us to theorize that the decision to apply for academic promotion is informed by a cost-benefit analysis, early career experiences, conformity with academic norms that over-emphasize research productivity, as well as access to career-advancing resources (especially time for research). We recommend that the gendered nature of the academic reward system be re-imagined to promote equality, and provide suggestions as to how to do so.